Caracterização molecular, cultural e patogênica de Didymella bryoniae de cucurbitáceas - Aguiar, Bárbara de Melo (2008)
Gummy stem blight, caused by the fungus Didymella bryoniae [anamorph: Ascochyta cucumis (syn.: Phoma cucurbitacearum) is an important disease of several species within the Cucurbitaceae family. The objective of this work was to determine the extent of molecular, cultural, and pathogenic variability among 21 D. bryoniae isolates from melon (Cucumis melo), cucumber (C. sativus), watermelon (Citrullus lanatus), and pumpkin (Cucurbita pepo). Additionally, it was evaluated the effect of grafting of susceptible cucumber on resistant pumpkin plants on control of gummy stem blight. The analysis of sequences of a portion of ribosomal DNA, containing the regions ITS1 and ITS2, and the 5.8 gene, allowed indirect identification of species; however, it was observed low variability among the isolates. The virulence of isolates was compared based on seven cucurbit genotypes (hybrids and varieties of cucumber, melon, and pumpkin), however the ranks of isolates were not consistent among the genotypes. The interaction between host genotypes and isolate, based on the analysis of four isolates (two isolates from cucumber and two isolates from melon) and seven host genotypes (four cucumber and three melon genotypes) was not significant for stem gummy, but was significant for leaf spot (P=0,05). It was not observed relationship among Virulence, cultural characteristics and phylogenetic grouping among the tested isolates. Grafting susceptible cucumber on resistant pumpkin reduced severity of stem gummy blight on cucumber.